Acquisition Recommendations For Pt Jaya Agra Wattie Tbk. And Clustering Analysis Of Plantation Industry In Indonesia Based On Financial Statement & Ratio For Period Of January 2021-2022 - Hanifa, Hanifa; Madiistriyatno, Harries (Aliansi : Jurnal Manajemen dan Bisnis, 2023)
In Indonesia, plantation industry has an important role in nation's economic growth. One of them is PT Jaya Agra Wattie (JAWA) Tbk., a company established for more than 100 years indicating that there were financial problems having impact on the company's performance. Therefore, the researcher recommends that the JAWA should be acquired, so that this company could remain establishing and become a supporter of economic growth. The researcher used K-Means Clustering method with Financial Ratio, Debt Equity Ratio (DER), Price to Book Value (PBV), and Return on Equity (ROE).